Otological complications in inversa type recessive dystrophic epidermolysis bullosa. (1st April 2022) - Robertson, S. J.; Prodinger, C.; Liu, L.; Skilbeck, C.; Petrof, G.; Martinez, A. E.; Mellerio, J. E.; Greenblatt, D. T.
Summary: Background: The rare inversa subtype of recessive dystrophic epidermolysis bullosa (RDEB‐I) is characterized by predominant intertriginous skin blistering and marked mucosal involvement. Specific recessive missense mutations in the collagen VII triple helix are implicated in the disease. To date, otological complications have been reported infrequently in this patient group. Methods: We conducted an observational, retrospective, double institution case record review of patients with RDEB‐I who presented with otological complications between January 2000 and June 2020. Diagnosis was established on the basis of clinical features, family history and mutation analysis of the COL7A1 gene. Results: In total, 11 (44%) of 25 patients with RDEB‐I in our database (2 paediatric, 9 adult; mean age 40.9 years, range 8–72 years) experienced otological complications. Of these 11 patients, 10 (90.9%) had recurrent otitis externa, 7 (63.6%) had meatal stenosis and 7 (63.6%) had recurrent blistering of the external auditory canals. All 11 patients reported hearing difficulties, with conductive hearing loss confirmed by audiology testing in 6 (54.5%) of these. Of the 11 patients, 3 (27.3%) went on to have implantable hearing aids [2 bone‐anchored hearing aids (BAHA) and 1 middle ear implant (MEI)] fitted with favourable outcome, while a fourth paediatric patient presented with a cholesteatoma that was surgically managed. Discussion: We observed a higher prevalence of otological morbidity in RDEB‐I than previously reported, and present the first case of cholesteatoma in epidermolysis bullosa (EB). Our data indicate that BAHA and MEI are safe and effective treatment options for hearing loss in EB. Clinicians should be vigilant in screening for ear symptoms in RDEB‐I and consider early referral to an Ear, Nose and Throat specialist. Abstract : We present otological complications in the rare inversa subtype of recessive dystrophic epidermolysis bullosa, as well as experience with bone anchored hearing aids in this subgroup.